Formation of the package of materials of adaptive multifunctional clothing - Buhantsova, Ludmyla; Luschevska Оlena; Troyan, Oleksandr; Krasnіuk Larysa; Yantsalovskyі Оleksandr (Technology audit and production reserves, 2017)
The object of research is the process of designing of adaptive multifunctional clothing. The problematic issue of the object is to ensure its effectiveness through properties. The basis for improvement of designing of adaptive multifunctional clothing is the application of energy-information effects of materials on the functional state of the human body. On the basis of this, it is justified to form a package of materials for development of adaptive men’s underwear for treatment and prevention of chronic prostatitis. Selected paintings have a high inertness level for the functional state of the human body 0.87...1.0. Positive energy-information impact on the functional state of the body is achieved due to the influence of silver plates located in the product, according to certain biologically active zones of the human body. For a reasonable choice of the technology of joining materials and means of energy-information impact, the thickness of the overhead seams is studied. The rationale is that by increasing the design thickness of the package of materials by 32 %, the thickness of the seam increases by 28.8 %. The effectiveness of the developed adaptive multifunctional underwear is confirmed by experimental wearing and clinical approbation. It is determined that the functional state of the male patients improved after the use of developed clothing for one month. The conducted researches ensure the provision of adaptive multi-functional clothing with expanded functional capabilities that has a positive social and economic effect.